Democracy for All: Conceptualizing and Measuring Egalitarian Democracy. Issue 3 (18th April 2018) - Sigman, Rachel; Lindberg, Staffan I.
Abstract : Although equality figures prominently in many foundational theories of democracy, liberal and electoral conceptions of democracy have dominated empirical political science research on topics like political regimes, democratization and democratic survival. This paper develops the concept of egalitarian democracy as a regime that provides de facto protection of rights and freedoms equally across the population, distributes resources in a way that enables meaningful political participation for all citizens and fosters an environment in which all individuals and social groups can influence political and governing processes. Using new indicators from the Varieties of Democracy project, the paper develops and presents measures of these important concepts, demonstrates their relationship to existing measures, and illustrates their utility for advancing the study of democracy in ways that more fully embrace the richness of democratic theory.